Serum Progesterone Profile Across the Mid and Late Luteal Phase in Artificial Cycles Is Associated With Pregnancy Outcome - Labarta, Elena; Rodríguez-Varela, Cristina; Mariani, Giulia; Bosch, Ernesto (Frontiers in Endocrinology, 2021)
Introduction: Recent studies have shown that low serum progesterone levels on the day of embryo transfer (ET) are associated with poorer pregnancy outcome in hormonal replacement therapy cycles. It is of interest to know if serum progesterone levels during late luteal phase (following days after ET) are also related with the chances of ongoing pregnancy. Objective: To evaluate the luteal phase endocrine profile through measurements of serum progesterone and estradiol on days ET+4, ET+7 and ET+11, to test their predictive value in relation to pregnancy outcome. Setting: Private infertility center, Valencia, Spain. Materials and Methods: Prospective cohort study performed between June 2017 and August 2018. Eligible patients were aged between 18-42 years, with a normal uterus, and being transferred 1-2 good quality blastocysts in a frozen ET cycle after an artificial endometrial preparation with estradiol valerate and vaginal micronized progesterone (400 mg/12 hours). Results: A total of 127 patients were included. Mean age=38.0±3.9 years; BMI=23.6±3.6 kg/m2; endometrial thickness=9.1±1.6mm. Overall ongoing pregnancy rate=47.2% (95%CI:38.3-56.3). Significantly higher levels of serum progesterone were observed on ET+4 (13.6±6.0 vs. 11.1±4.6ng/ml, p=0.03) and ET+11 (15.7±1.2 vs. 10.3±0.6ng/ml, respectively; p=0.000) in ongoing pregnancies versus negative β-hCG cases. On ET+7, ongoing pregnancies also had higher serum progesterone levels (14.2±0.9 vs. 11.7±0.8ng/ml, but did not reach statistical significance (p=0.07). Serum estradiol levels were not related with pregnancy outcome at any moment of the luteal phase (p>0.05). On days ET+4, +7 and +11, the ROC analysis showed that serum progesterone levels were predictive of ongoing pregnancy, and Pearson’s coefficient showed a significant association (p<0.05) of serum β-hCG levels with serum progesterone. Conclusions: In hormonal replacement therapy cycles, serum progesterone levels across luteal phase days are associated with pregnancy outcome. Ongoing pregnancies were associated with a higher exposure to progesterone in comparison with pregnancy losses or negative β-hCG. Therefore, serum progesterone might be playing an important role not only during implantation, but also in pregnancy maintenance. It remains unknown if the variability in serum progesterone levels among patients, after receiving the exact same progesterone dose for luteal phase support, is the cause or just a consequence of pregnancy results.